Rancangan Game RPG ”Legenda Putri Petung” Menggunakan RPG Maker MV - Arham, Muhammad Agus Faadhilah; Fajri, Ahmad; Wahyuni, Wahyuni (Journal of Informatics, Electrical and Electronics Engineering, 2025)
Games have become a popular entertainment alternative for various groups, with very rapid development. This research focuses on the creation of a Role-Playing Game (RPG), which is known for its complex story elements and strong role immersion. The purpose of this research is to develop an RPG based on the East Kalimantan folktale "Legenda Putri Petung" using RPG Maker MV software. Through this game, it is hoped that the folktale can become known and preserved by the younger generation. The development method used is the System Development Life Cycle (SDLC) with the stages of planning, design, implementation, and testing. In the Planning stage, goal identification and requirement gathering were conducted. The Design stage included designing the story flow, characters, and game world. In the Implementation stage, all designs were realized into RPG Maker MV. The final stage was Testing, to ensure the game functions well and is free from errors. The result of this research is the creation of the RPG "Legenda Putri Petung," which has been enriched with collaborations from characters in other folktales to avoid a monotonous impression. Thus, this game successfully serves as an effective medium for introducing and preserving the "Putri Petung" legend in an engaging and interactive format.